EVALUATION OF THE IMPACT OF INNOVATIONS IN INCREASING LABOR EFFICIENCY IN SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Kuziyeva Gulnoza Rashidovna (Labor economics and human capital, 2024)
The article analyzes the role and significance of innovations in increasing labor productivity in small businesses and private entrepreneurship. It highlights the impact of innovative approaches such as the implementation of modern technologies, automation of production processes, and digitalization of labor operations on improving labor efficiency. The author emphasizes the opportunities for strengthening the competitiveness of entrepreneurial entities, optimizing costs, and improving product quality by enhancing labor productivity. The strategic importance of innovations in entrepreneurship for adapting to changing market demands is substantiated with examples and statistical data.